Ensuring sustainable energy as a sign of environmental responsibility and social justice in European Union members - Kryk, Barbara (Economics and Environment, 2019)
The article aims to measure and assess the degree of providing sustainable energy in the European Union (EU) countries in the context of social and environmental responsibility and social justice as well as in the context of implementation of the 7th goal of Agenda 2030. Providing people with access to sustainable energy and increasing energy efficiency in all sectors of the economy isnecessary to achieve the goals of the concept of sustainable development, the Agenda 2030, the Europe 2020 strategy, and the European energy policy. Ensuring sustainable energy is also a sign of environmental responsibility and social justice. Accurate evaluation of achievements in this area is a relatively new issue, both in economic practice and in modern economics, therefore, there is a need to develop ways for measuring access to sustainable energy other than the usual analysis of time-seriesof data in individual years, on which current studies are based. Hence, an attempt was made to use two methods belonging to cluster analysis (Ward method and k-means) in order to more effectively assess the degree of sustainable energy provision undertaken by EU countries. This is a novel approach in this area as it directs the article towards the research trend focused on the operationalization of the concept of sustainable development. In the study, available statistical data on 8 indicators for SDG 7,reported by Eurostat and established by the UN, were used, covering the years 2010 and 2016. The study enabled the grouping of EU countries by the degree of provision of sustainable energy and, thus, the determining of their environmental responsibility and social justice in this area. The study shows that past EU achievements in providing sustainable energy are not particularly spectacular; there is no country where they were completely satisfactory, they were quite satisfactory in only 14 countries,averagely satisfactory in 9 countries, and unsatisfactory in 5 countries.